Pengembangan Media Pembelajaran Hole Adventure Untuk Meningkatkan Keterampilan Menulis Cerpen Siswa - Fika Dewi (The Elementary Journal, 2026)
This research examines the importance of competencies in the Pancasila Student Profile, especially creativity. Teachers can foster creative learning by designing innovative media that encourages students’ creativity. The method used includes Research and Development (R&D) with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) approach. The data was gathered through unstructured interviews, non-participant observation, a questionnaire, and an assessment, including pre-test and post-test. This research aims to (1) develop an audio-visual digital short story learning medium titled “Hole Adventure,” (2) analyse its impact on improving creative writing skills. Based on this research, the implementation of the learning media towards 5th grade students of MIM Plus Suwaru Bandung in Tulungagung shows a significant improvement in creative writing skills. It resulted the value p < 0.001, indicating positive impact of using "Hole Adventure" media learning.